2010
DOI: 10.1111/j.1365-2559.2010.03480.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological features and CD57 expression in renal cell carcinoma in acquired cystic disease of the kidneys: with special emphasis on a relation to the duration of haemodialysis, the degree of calcium oxalate deposition, histological type, and possible tumorigenesis

Abstract: ACDK-RCCs reveal characteristics of Henle's loop, which may be related to their peculiar pathological features, including intratumoral oxalate deposition and cyst and AC formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 27 publications
3
31
0
1
Order By: Relevance
“…20,21 In some recent publications, a long duration of dialysis (>10 y) has had a stronger association with ACD-RCC compared with other subtypes of RCC arising in this setting, [22][23][24] although such an association was not identified in another large series. 5,[20][21][22]24,25 Most tumor cells have abundant granular eosinophilic cytoplasm, with round to oval nuclei showing vesicular chromatin and prominent nucleoli. The noncystic tumors are well circumscribed and may be surrounded by a thick fibrous capsule showing dystrophic calcification.…”
Section: Proposed New Epithelial Neoplasms Tubulocystic Renal Cell Camentioning
confidence: 94%
See 1 more Smart Citation
“…20,21 In some recent publications, a long duration of dialysis (>10 y) has had a stronger association with ACD-RCC compared with other subtypes of RCC arising in this setting, [22][23][24] although such an association was not identified in another large series. 5,[20][21][22]24,25 Most tumor cells have abundant granular eosinophilic cytoplasm, with round to oval nuclei showing vesicular chromatin and prominent nucleoli. The noncystic tumors are well circumscribed and may be surrounded by a thick fibrous capsule showing dystrophic calcification.…”
Section: Proposed New Epithelial Neoplasms Tubulocystic Renal Cell Camentioning
confidence: 94%
“…20 The tumors often appear as nodules arising from cyst walls, occasionally completely filling these cysts, or as solid masses separate from the cysts. One characteristic feature is the presence of intracellular and/or intercellular microscopic lumina (holes), imparting a cribriform/sieve-like appearance 5,20,22,24,25 (Fig. Cut surfaces are tan to yellow, and hemorrhage and necrotic/friable areas are commonplace.…”
Section: Proposed New Epithelial Neoplasms Tubulocystic Renal Cell Camentioning
confidence: 99%
“…The accumulation of small amounts of calcium oxalate crystals in the absence of aberrant oxalate metabolism has been termed dystrophic oxalosis [28]. This has been reported in a number of tissues including arterial atherosclerotic plaques, myocardium, lymph nodes, testis, thyroid, breast, ocular tissues, and kidneys with acquired cystic disease [28, 29]. In the study of calcium oxalate deposits in coronary artery atherosclerotic plaques, the 4 patients all had chronic diseases that can increase oxidative stress levels, including AIDS, hepatitis C, sepsis, ischemic heart disease, and cancer [28].…”
Section: Calcium Oxalate In Tissuesmentioning
confidence: 99%
“…For example, end-stage renal disease is associated with oxidative stress. Enoki et al reported that oxalate deposition in the kidneys of patients with acquired cystic disease was positively correlated with the number of months being on dialysis [29]. …”
Section: Calcium Oxalate In Tissuesmentioning
confidence: 99%
“…La plupart du temps il s'agit d'une tumeur de découverte fortuite. Selon certaines publications, il existerait un rapport entre la durée de la dialyse (> 10 ans) et le développement de cette tumeur mais les résultats sont encore contradictoires [7,8]. Macroscopiquement, il s'agit de nodules bien encapsulés se développant au sein des kystes.…”
Section: Carcinome Rénal Associé à Une Maladie Rénale Kystique Acquiseunclassified